A Metal Chelating Porous Polymeric Support: The Missing Link for a Defect‐Free Metal–Organic Framework Composite Membrane - Barankova, Eva; Tan, Xiaoyu; Villalobos, Luis Francisco; Litwiller, Eric; Peinemann, Klaus‐Viktor (Angewandte Chemie International Edition, 2017)
Since the discovery of size‐selective metal–organic frameworks (MOFs), researchers have tried to incorporate these materials into gas separation membranes. Impressive gas selectivities were found, but these MOF membranes were mostly made on inorganic supports, which are generally too bulky and expensive for industrial gas separation. Forming MOF layers on porous polymer supports is industrially attractive but technically challenging. Two features to overcome these problems are described: 1) a metal chelating support polymer to bind the MOF layer, and 2) control of MOF crystal growth by contra‐diffusion, aiming at a very thin nanocrystalline MOF layer. Using a metal chelating poly‐thiosemicarbazide (PTSC) support and adjusting the metal and organic ligand concentrations carefully, a very compact ZIF‐8 (ZIF=zeolitic imidazolate framework) layer was produced that displayed interference colors because of its smooth surface and extreme thinness—within the range of visible light. High performances were measured in terms of hydrogen/propane (8350) and propylene/propane (150) selectivity. Thin‐film interference: An extremely thin, smooth, and defect‐free zeolitic imidazolate framework (ZIF‐8) layer displays interference colors similar to an oily film on water. The film was grown on top of a metal‐chelating polymer; the thickness was controlled by a contra‐diffusion preparative method.